2013
DOI: 10.4067/s0718-93032013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Los signos de puntuación en español: cuestiones de uso y errores frecuentes

Abstract: The current paper aims to analyze how first year university students of the Spanish Language and Literature Degree use punctuation marks. For this purpose, a sample of 128 interventions was collected. The discursive frame where participations took place was the academic virtual forum; particularly, two thematic forums were provided. Results show that comma and full stop are the most usual punctuation marks; it is also significant the high frequency with which English inverted commas appear in the written texts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
3
0
4
Order By: Relevance
“…Estas reglas tienden a buscar una relación entre lo que se escribe y los aspectos sonoros del habla, lo que no siempre se corresponde de manera exacta. Es lo que ocurre en el caso de la puntuación en que la norma ha evolucionado, llegando a combinar criterios fónicos con criterios sintáctico-semánticos (Real Academia Española, 2010;Rodríguez y Ridao, 2013). Por último, la mayor frecuencia de puntuación interna en el cuento, en comparación con la carta y la noticia, podría estar asociada a que estos últimos fueron textos más breves y, en la mayoría de los casos, escritos en un solo párrafo.…”
Section: Resultados Según Variables De Sexo Y Gseunclassified
See 1 more Smart Citation
“…Estas reglas tienden a buscar una relación entre lo que se escribe y los aspectos sonoros del habla, lo que no siempre se corresponde de manera exacta. Es lo que ocurre en el caso de la puntuación en que la norma ha evolucionado, llegando a combinar criterios fónicos con criterios sintáctico-semánticos (Real Academia Española, 2010;Rodríguez y Ridao, 2013). Por último, la mayor frecuencia de puntuación interna en el cuento, en comparación con la carta y la noticia, podría estar asociada a que estos últimos fueron textos más breves y, en la mayoría de los casos, escritos en un solo párrafo.…”
Section: Resultados Según Variables De Sexo Y Gseunclassified
“…En su origen, la puntuación refiere a una serie de signos escritos, distintos de los grafemas, cuyo propósito es dar cuenta de los rasgos prosódicos del lenguaje oral (pausas, entonación) a fin de facilitar la comprensión de lo escrito (Rodríguez y Ridao, 2013 Evaluación analítica de la escritura de estudiantes de 4º año básico en Chile fonético y en la relación entre lo que se escribe y los aspectos sonoros del habla. En la misma perspectiva, Kaufman (2005) resalta la dificultad que supone la ortografía (en este caso la ortografía puntual), debido a que incluye muchas reglas y datos que no son reflejados por la sonoridad.…”
Section: Puntuaciónunclassified
“…We have shown that: (1) secondary-education students often struggle with the placement of commas in sentences, and (2) the correct use of commas is associated with reading comprehension in a silent reading scenario. At this educational level, most research has focused on testing whether students have learned the grammatical rules of comma usage (e.g., [ 13 , 14 ]). We believe that teaching the use of commas should not be limited to learning grammatical rules but should also be related to their function.…”
Section: Discussionmentioning
confidence: 99%
“…These issues also arise for university students. Rodríguez Muñoz and Ridao Rodrigo [ 14 ] analyzed 128 writings of first-year university students in forums for two courses. The comma presented a percentage of use of only 47%.…”
Section: Introductionmentioning
confidence: 99%
“…and "¡!". However, influenced by English and the keyboards used on many electronic devices, written CMC increasingly contains only the closing exclamation and interrogation signs (Galán 2002;Ridao and Rodríguez 2013). Similarly, the accent mark is rarely used: the interrogative pronoun qué ('what') should carry the accent mark, but seldom does in Twitch chats, and the same applies to words like aquí ('here') or música ('music'), as shown in Figure 7 (y esta musica?).…”
Section: Non-normative Orthography and Strange Typographical Formsmentioning
confidence: 99%